STATUS PESANTREN MUâADALAH; Antara Pembebasan dan Pengebirian Jatidiri Pendidikan Pesantren - Bukhory, Umar (STAIN PAMEKASAN, 2012)
AbstractIslamic boarding school is the oldest Islamic education institution in Indonesia. from the perspective of politic, the existency of Islamic boarding school has just been admitted by the post-reformationÂ government. It is declared on the article ofÂ UU No. 20 Tahun 2003 about SISDIKNAS, the establishment of special directorate in Religious Affairs departement, the publishment ofÂ various law products, and muâÃ¢dalah (equality) toward some Islamic boarding schools. This article describes the problem of independecy and the diversity of Islamic boarding school educational systems after the publishment of the law products. undangan tersebut.Kata-kata kuncimuâadalah, pondok pesantren, pembaharuan kependidikan pesantren